Analyzing Control Levels In Performance Based Budgeting Within The Public Sector - Marini Sari Dewi Seger (Journal of Governance and Administrative Reform, 2026)
Abstract Performance-based budgeting has been adopted as an instrument of public financial reform to strengthen accountability and improve the effectiveness of government spending. However, its implementation in the public sector continues to reveal an imbalance between accountability demands and the dominance of administrative control. The low achievement of several performance indicators and weak public participation indicate structural problems in the design of control mechanisms within performance-based budgeting. This study aims to analyze the sources and degrees of control in the public sector performance-based budgeting system. A descriptive qualitative approach was employed through a systematic literature review, using Romzek and Dubnick’s analytical framework, which classifies control according to its source (internal–external) and degree (high–low). The findings show that performance-based budgeting practices remain dominated by high-degree internal control, particularly hierarchical and legal control, while external control, especially political, professional, and public control, remains weak and has not been effectively institutionalized. This imbalance limits managerial flexibility and hinders the transition of performance-based budgeting toward results-based budget accountability. The study highlights the importance of strengthening external control as a prerequisite for improving the effectiveness and legitimacy of performance-based budgeting reforms.   Keywords: performance based budgeting; control; public sector.